Tinjauan Ekonomi Islam Terhadap Jual Beli Online Furniture Dengan Akad As-Salam (Studi Kasus Nayyara Perabot Mandailing Natal) - Etika Manda Sari Rangkuti; Sri Sudiarti; Nursantri Yanti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
“Salam” is a transaction or sales contract in which the goods being sold have not yet been obtained at the time of the transaction. The buyer makes an upfront payment, and the delivery of the goods is carried out at a later date. This research is motivated by the practice of online merchants in the Mandailing Natal district in applying a trade system based on orders and whether it complies with the concept of “as-salam” as defined by Islamic economics. The data for this research was collected through interviews and documentation. Initially, the author conducted direct observations at the research location to closely obserbe what was happening. Subsequently, interviews were conducted with the owners of furniture businesses and some consumers of Nayyara Perabot to obtain strong data. The data collected by the researcher was analyzed using qualitative analysis methods, including data reduction, data presentation, drawing conclusions, and authenticity testing. Based on the research findings, in online sales with “salam” contracts for furniture at Nayyara Perabot in Mandailing Natal, the practices that have been followed so far are in line with the concept of “salam”. This includes the spesification of ordered goods, the agreed-upon delivery time and location, and the satisfaction of consumers upon receiving the goods.